Pengenaan Pajak Penghasilan Pada Aktivitas Endorsement Yang Dilakukan Oleh Pegiat Media Sosial - Robiatul Adawiyah; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2025)
Endorsements are highly effective social media ads. In the modern business world, endorsement is an activity of business owners asking celebrities to promote products through their social media channels. This study covers two issues, namely how the regulation of income tax collection for authentication activities in Indonesia and how the application of income tax to tax subjects in authentication activities. Negative legal research is the type of research used in this study. Promotional activities through social networks are a form of service use for individuals, so the applicable tax rate is Income Tax. The income tax regulation is regulated in Article 4 of Law No. 36 of 2008 concerning Income Tax which explains that the object of taxation is income. On this basis, it is necessary to collect tax on sponsorship activities on social networks.